Pengaruh Web Based E-Learning Terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran Simdig di SMKN 1 Sungai Aur - Puja, Rohaya Fauza; Zakir, Supratman (Indonesian Research Journal on Education, 2023)
The purpose of this study was to determine whether there is an effect of Web-Based E-learning on thelearning outcomes of class X students in the Simdig subject at SMKN 1 Sungai Aur. Web Based Elearning is an integrated software/programme that automates the administration, tracking andreporting system of learning in scheduling and organizing students. Where the problem is the lack ofenthusiasm of students when online because the teacher only uses WhatsApp as a learning medium, theteacher is difficult to control and get the focus of students, students do other things when onlinelearning takes place such as playing games and others, and Growing boredom of students because theteacher provides material, asks students to read. Then give a task with a certain deadline.‎The type ofresearch used by the author is correlation with the quantitative data processing process. Thepopulation taken is class X majoring in Tbsm 1, Tbsm 2, Aphp 1 and sampling is carried out using nonprobability sampling technique. The research instrument is in the form of a questionnaire and has beentested for validity‎ with rcount > rtable which means valid and reliability test 0.907>0.06 which meansreliable.‎ The results after being processed using SPSS obtained R2 is 0.761 which means that H1 isaccepted H0 is rejected, namely "there is an influence of Web Based E-learning of 76.1% on the resultsof class X students in the subjects of simdig lessons at SMKN 1 Sungai Aur So, the use of Web Based Elearning during the COVID-19 pandemic is effectively used as a learning medium during the learningprocess so that student learning outcomes increase. ‎‎